HUBUNGAN KEBIASAAN MINUM DENGAN STATUS HIDRASI DAN KEBUGARAN JASMANI PADA ATLET DI PERSATUAN BULUTANGKIS KABUPATEN KUDUS - ariantika, aprilia; Mardiyati, Nur Lathifah (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2017)
The purpose of this research is to know the correlation of drinking habit with hydration status and physical fitness of athlete in Badminton Association of Kudus Regency. This type of observational research with cross sectional approach. The number of research subjects is 33 athletes consisting of three badminton clubs in Kudus District, namely PB Taurus, PB Putra Sang Fajar and PB Djarum Kudus. Sampling using simple random sampling method. Taking data on drinking habits is obtained with Food Frequency Questionnaire (FFQ). The hydration status is obtained by card measurement PURI (Check Your Own Urine). Physical fitness is derived from a physical fitness test that is a Beep test. Test the relationship using Spearmen Rank Test and Pearson Product Moment Test. Research subjects who have drinking habits less 48,5%, enough 15,2% and more 36,4%. Dehydrated athletes weigh 9,1%, mild dehydration 60,6% and well hydrated 30,3%. Athletes who have physical fitness under 12,1% average, 12,1% average, above average 24,2%, Excellent 30,3% and Superior 21,2%. The correlation between drinking habit and hydration status was obtained (p=0,000, r=0,589) and the relationship between drinking and physical fitness was obtained (p=0,459). Conclusion In this study there is a relationship between drinking habits with hydration status and no relationship between drinking habits and physical fitness. Advice for athletes is expected to know the factors that affect dehydration and its effects.